Cerebrospinal fluid camk2a levels at baseline predict long-term progression in multiple sclerosis - Sohaei, Dorsa; Thebault, Simon; Avery, Lisa M.; Batruch, Ihor; Lam, Brian; Xu, Wei; Saadeh, Rubah S.; Scarisbrick, Isobel A.; Diamandis, Eleftherios P.; Prassas, Ioannis; Freedman, Mark S. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Multiple sclerosis (MS) remains a highly unpredictable disease. Many hope that fluid biomarkers may contribute to better stratification of disease, aiding the personalisation of treatment decisions, ultimately improving patient outcomes. Objective The objective of this study was to evaluate the predictive value of CSF brain-specific proteins from early in the disease course of MS on long term clinical outcomes. Methods In this study, 34 MS patients had their CSF collected and stored within 5 years of disease onset and were then followed clinically for at least 15 years. CSF concentrations of 64 brain-specific proteins were analyzed in the 34 patient CSF, as well as 19 age and sex-matched controls, using a targeted liquid-chromatography tandem mass spectrometry approach. Results We identified six CSF brain-specific proteins that significantly differentiated MS from controls (p < 0.05) and nine proteins that could predict disease course over the next decade. CAMK2A emerged as a biomarker candidate that could discriminate between MS and controls and could predict long-term disease progression. Conclusion Targeted approaches to identify and quantify biomarkers associated with MS in the CSF may inform on long term MS outcomes. CAMK2A may be one of several candidates, warranting further exploration.